Evaluating Management Framework Selection: An Analysis of Position-Job Management Spectrum in Digital Era - Swetha Priya Sathiyam, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the strategic considerations organizations face in selecting and implementing management frameworks, specifically focusing on the spectrum between Position Management and Job Management approaches. Through a comprehensive analysis of implementation patterns in various sectors, this article explores how different industries approach workforce structuring based on their unique operational demands. Position Management emerges as a framework particularly suited for regulated industries requiring strict hierarchical structures and compliance oversight, while Job Management demonstrates significant advantages for dynamic, growth-oriented environments. It synthesizes insights from healthcare, government, technology, and startup sectors, revealing how framework selection impacts organizational agility, resource allocation, and long-term workforce planning capabilities. Furthermore, it introduces systematic approaches to framework selection and implementation, emphasizing the importance of organizational learning and adaptation in framework evolution. This comprehensive article provides practitioners and researchers with structured approaches to evaluate and implement management frameworks aligned with organizational objectives while maintaining adaptability in an evolving business environment.
Keywords: Position Management Framework; Organizational Structure Design; Job Management Systems; Framework Implementation Strategy; Workforce Planning Methodology